Electrical performance of bifacial silicon PV modules under different indoor mounting configurations affecting the rear reflected irradiance. (1st January 2019) - Lopez-Garcia, Juan; Casado, Alberto; Sample, Tony
Highlights: Electrical performance of c-Si bifacial PV modules under different configurations. Reflective rear panel as potential double-sided illumination characterization method. Increase up to 20% P max with reflective rear panel under specific conditions. Rear irradiance non-uniformity need to be improved to match IEC60904-1-2 requisite. Agreement between single-side and double-side illumination approaches. Abstract: Bifacial photovoltaic (PV) modules can increase the performance with respect to traditional PV modules because both sides of the cells, front and rear, absorb solar radiation. To assess their performance and quality, PV modules are characterized using international standards. However, currently only a draft IEC technical specification exists for bifacial PV modules and research needs to be done in order to study the indoor performance testing conditions. One of the issues that need to be addressed is how to measure bifacial PV modules correctly and analyse the different testing approaches proposed. This work outlines the indoor performance testing of c-Si bifacial modules under different module mounting setups including open rack, a structure with baffles and 3 modules. For each mounting method a white reflective rear panel of several dimensions was placed at various distances behind the module as a potential approach for a double-sided illumination characterization method. Electrical performance is also studied with a single-side illumination method with a black rear panel. The rear irradiance measurements and non-uniformity are also studied and the performance measurements are validated with a single-side illumination method. Additional rear irradiance allows P max increment up to 20% under certain conditions. However, the rear irradiance non-uniformity needs to be improved in order to fulfil the current requirements of the draft technical specification.